Phenomenology of the exercise of freedom a proposal from logotherapy and existential analysis - Salomón Paredes, Alejandro Khaled (2021)
In this article, a descriptive investigation of the phenomenon of freedom is carried out in the first person, from a phenomenological logotherapeutic orientation, which emphasizes the experience of self-understanding regarding what specifically constitutes being human and opens the being to existence: awareness of the ability to choose and responsibility towards oneself and their circumstances. The absence of this self-understanding leaves the person at the mercy of nature, learning, society, and destiny. The existential task then consists of achieving that selfknowledge and assuming the leading role in one’s life. Existing implies not only being free, but daring to exercise freedom, recognizing in the midst of dissatisfaction and anguish the human condition of being confronted with everything, a fundamental principle of being free. For this purpose, authors such as Viktor E. Frankl, Max Scheler, Martin Heidegger, Karl, Jaspers, Sören Kierkegaard, Rudolf Allers, among others, have been used.